Localization and Ordering of Lipids Around Aquaporin-0: Protein and Lipid Mobility Effects - Briones, Rodolfo; Aponte-Santamaría, Camilo; de Groot, Bert L. (Frontiers in Physiology, 2017)
Hydrophobic matching, lipid sorting, and protein oligomerization are key principles by which lipids and proteins organize in biological membranes. The Aquaporin-0 channel (AQP0), solved by electron crystallography (EC) at cryogenic temperatures, is one of the few protein-lipid complexes of which the structure is available in atomic detail. EC and room-temperature molecular dynamics (MD) of dimyristoylglycerophosphocholine (DMPC) annular lipids around AQP0 show similarities, however, crystal-packing and temperature might affect the protein surface or the lipids distribution. To understand the role of temperature, lipid phase, and protein mobility in the localization and ordering of AQP0-lipids, we used MD simulations of an AQP0-DMPC bilayer system. Simulations were performed at physiological and at DMPC gel-phase temperatures. To decouple the protein and lipid mobility effects, we induced gel-phase in the lipids or restrained the protein. We monitored the lipid ordering effects around the protein. Reducing the system temperature or inducing lipid gel-phase had a marginal effect on the annular lipid localization. However, restraining the protein mobility increased the annular lipid localization around the whole AQP0 surface, resembling EC. The distribution of the inter-phosphate and hydrophobic thicknesses showed that stretching of the DMPC annular layer around AQP0 surface is the mechanism that compensates the hydrophobic mismatch in this system. The distribution of the local area-per-lipid and the acyl-chain order parameters showed particular fluid- and gel-like areas that involved several lipid layers. These areas were in contact with the surfaces of higher and lower protein mobility, respectively. We conclude that the AQP0 surfaces induce specific fluid- and gel-phase prone areas. The presence of these areas might guide the AQP0 lipid sorting interactions with other membrane components, and is compatible with the squared array oligomerization of AQP0 tetramers separated by a layer of annular lipids.